Prospects for the Utilization of Eco-Enzymes in the Cultivation of Environmentally Friendly Red Ginger Plants in Ngentak Hamlet, Samigaluh, Kulon Progo DIY - Okti Purwaningsih; Puguh Bintang Pamungkas; Rahmat A Hi Wahid (LPPM UIKA Bogor, 2022)
Yard land has the potential to be developed in order to produce a variety of foodstuffs to medicines, which can be consumed by family members. Utilization of yards can be initiated by KWT Sumber Rejeki, Ngentak Village, by cultivating red ginger plants using a healthy farming system with Eco-enzyme fertilizer application. A healthy farming system is a cultivation system that minimizes the input of chemicals on cultivated land, so as to maintain the quality of the environment and agricultural products produced. Selection of ginger plants for cultivation in the yard, because the ginger plant can be used for spices, traditional medicine, ginger candy, candied ginger, instant drinks, pickled ginger, ginger coffee, ginger syrup, and as an export commodity. The results of the socialization and mentoring carried out, information was obtained that most of the members of Sumber Rejeki KWT have received socialization on medicinal plant cultivation, but they do not know how to cultivate medicinal plants properly, in general, the cultivation of medicinal plants is only planted in moderation, there is no land cultivation and plant maintenance, even though the selection of seeds, processing of planting media and care are very important to produce quality plants. After the socialization and training on ginger cultivation was held, most of the members of KWT Sumber Rejeki were interested in cultivating red ginger in their home gardens, because red ginger plants are able to provide benefits to the community not only in terms of health, but also in terms of finance.